Peningkatan Ketetampilan Menyimak Di Sekolah Dasar Melalui Media Gambar, Digital, Dan Audio Visual - Fatkhia Nur Azizah; Sofia Nanda Saputri; Dina Puspita Anggraini; Nur Amelia Sari; Bayu Purbha Sakti (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Listening ability is one of the basic skills that must be mastered by elementary school students in learning Indonesian. However, in reality, students' listening ability is still relatively low. This article aims to examine various learning strategies and media used to improve elementary school students' listening skills through literature studies. The research method used is a qualitative approach with a literature review from various scientific sources. The results of the study show that learning media such as storytelling pictures, digital storytelling, wayang cerita and audio-visual media can significantly increase students' interest, understanding, and active participation in listening activities. The application of appropriate and innovative media has a positive impact on improving listening skills and supporting the achievement of Indonesian language learning objectives at the elementary level.